Innovaatiotoiminta: Suomi globaalitaloudessa - Jari Hyvärinen (The Research Institute of the Finnish Economy (ETLA), 2011)
– This study analyses those country characteristics, which lead those regions to become as productive operation and innovation environments for firms and research centres. This study shows that those countries who invest wisely to develop their innovation environment will be successful in high technology export markets. In recent years, Finnish high technology exports have declined because of difficulties in telecommunication sector. Productivity analysis shows that high country-level R&D expenditures - as in Finland and the United States - have positive correlation with labour productivity in manufacturing. Moreover, labour productivity in manufacturing in OECD countries relates positively with FDI and R&D expenditure growth. Also the level of education and firm-level sophistication increase labour productivity. China's role as global production factory and exporter has increased during 2000s. For example, Japanese and the US companies are leading actors, which are offshored their operations to China. However, deepening European integration has liberated and expanded intra-EU27 trade.
Keywords: F12; F15; F23; F43; J24; L23; O31; O38; 330; productivity; global production sharing; innovation activities